Comparative evaluation of the antibacterial activity of red diode laser therapy and 0.2% chlorhexidine against Aggregatibacter actinomycetemcomitans on implant healing abutments: An ex vivo study - Soumee Sengupta; S Ganesh; S Meenakshi; Avinash Singh Bettahalli; Raghavendra M Rao; K N. Raghavendra Swamy (Wolters Kluwer Medknow Publications, 2023)
Aims: The intraoral microbiota has a high potential to undergo dysbiosis, causing inflammatory changes with respect to the tissues surrounding either a natural tooth or an implant. Thus, the longevity of implant prosthesis depends on a thorough implant decontamination protocol. Among all the techniques available for doing so, laser is garnering increasing popularity, owing to minimal bleeding, high efficiency, and faster healing. However, limited literature exists regarding the superiority of lasers over chlorhexidine (CHX), the indisputable gold standard antibacterial chemical agent. The aim of this study was to compare the percentage of bacterial reduction of Aggregatibacter actinomycetemcomitans from implant healing abutments post red diode laser therapy versus 0.2% CHX treatment. Settings and Design: The current study had an ex vivo, observational, case-control design. Materials and Methods: Patients reporting for the second stage of the implant surgery were taken as the source of data and the healing abutments, the clinical samples. Eleven patients were chosen with one intraoral implant serving as the test site for laser treatment and another, the control site for CHX treatment. Microbiological analysis was performed via quantitative real time polymerase chain reaction to compare the bacterial reduction percentage after each treatment. Statistical Analysis Used: Repeated measures ANOVA and independent sample t test were used. Results: The mean bacterial viability of the test group (laser) was 1.2%-1.6%, and 0.6%-1.4% for the control group (CHX). The former caused a mean bacterial reduction of 96.1% while the latter, 96.3%. Both the treatments caused a highly statistically significant reduction of viable bacterial counts (P = 0.001). However, when compared, there was no statistically significant difference in the bacterial reduction, when compared in between the two (P = 0.902). Conclusion: Laser treatment is at par with chemical implant surface decontamination. It can help bypass the complications of CHX and revolutionize the protocols for implant surface decontamination.